Atlantic salmon (Salmo salar L.) post-smolts challenged two or nine weeks after seawater-transfer show differences in their susceptibility to salmonid alphavirus subtype 3 (SAV3). Issue 1 (December 2016) - Jarungsriapisit, J.; Moore, L.; Taranger, G.; Nilsen, T.; Morton, H.; Fiksdal, I.; Stefansson, S.; Fjelldal, P.; Evensen, Ø.; Patel, S.
Abstract Background Pancreas disease (PD), caused by salmonid alphavirus (SAV), is an important disease affecting salmonid aquaculture. It has been speculated that Atlantic salmon post-smolts are more prone to infections in the first few weeks following seawater- transfer. After this period of seawater acclimatization, the post-smolts are more robust and better able to resist infection by pathogens. Here we describe how we established a bath immersion (BI) model for SAV subtype 3 (SAV3) in seawater. We also report how this challenge model was used to study the susceptibility of post-smolts to SAV3 infection in two groups of post-smolts two weeks or nine weeks after seawater - transfer. Methods Post-smolts, two weeks (Phase-A) or nine weeks (Phase-B) after seawater- transfer, were infected with SAV3 by BI or intramuscular injection (IM) to evaluate their susceptibility to infection. A RT-qPCR assay targeting the non-structural protein (nsP1) gene was performed to detect SAV3-RNA in blood, heart tissue and electropositive-filtered tank-water. Histopathological changes were examined by light microscope, and the presence of SAV3 antigen in pancreas tissue was confirmed using immuno-histochemistry. Results Virus shedding from the Phase-B fish injected with SAV3 (IM Phase-B) was markedly lower than that from IM Phase-A fish. A lower percentage of viraemia in Phase-B fish compared with Phase-A fish was also observed. Viral RNA in hearts from IM Phase-A fish was higher than in IM Phase-B fish at all sampling points (p  < 0.05) and a similar trend was also seen in the BI groups. Necrosis of exocrine pancreatic cells was observed in all infected groups. Extensive histopathological changes were found in Phase-A fish whereas milder PD-related histopathological lesions were seen in Phase-B fish. The presence of SAV3 in pancreas tissue from all infected groups was also confirmed by immuno-histochemical staining. Conclusion Our results suggest that post-smolts are more susceptible to SAV3 infection two weeks after seawater-transfer than nine weeks after transfer. In addition, the BI challenge model described here offers an alternative SAV3 infection model when better control of the time-of-infection is essential for studying basic immunological mechanisms and disease progression.